Law and internet - Galindo Ayuda, Fernando (2009)
Jointly with other professors, we began several interdisciplinary investigations aimed at establishing relations between the law and information technology. The central subject of the investigations was the legal communication, and more specifically, the study of the possibility of providing scholars, through thesaurus, with the storage and recovery of legal documentation, using the information and communication technologies as an auxiliary instrument. As soon as the internet was materialized, another type of research appeared, considering the requirements to be met to guarantee the rights of persons to freely communicate their thoughts in the recovery of or access to the information. The referred works were those dedicated to the management of electronic identification and signature. At present, we return to the idea of the thesaurus combining it with the idea of the signature, in an attempt to put into practice the goal of building a system that will allow —making use of the internet as much as possible— all citizens in the online society, free access to and the recovery of legal documentation. A task that is a consequence of the virtual qualities of the Internet: joint works, of a «collaborative» nature can be carried out among research groups engaged in law and information technology that will enable the referred wide and, at the same time, specific access. This was the starting point to establish the Legal Framework for the Information Society or LEFIS, an organization founded by the research group